Occurrence of legume caterpillar moth in soybeans in northern Brazil - Silva, Anderson Gonçalves da; Grigolli, José Fernando Jurca; Souza, Bruno Henrique Sardinha de; Farias, Paulo Roberto Silva; Ribeiro, Rafael Coelho; Alencar, João Rafael De Conte Carvalho de; El-Husny, Jamil Chaar (EntomoBrasilis, 2019)
Abstract: This study reports the first occurrence of legume caterpillar moth Selenisa sueroides (Guenée) (Lepidoptera: Noctuidae) attacking soybeans in northern Brazil, being the second record in this crop in the country. This report resulted from periodic monitoring of soybean pests and natural enemies using the beat cloth in the region of Paragominas, state of Pará, during the 2015-2017 seasons. The presence of S. sueroides larvae was recorded in all crop seasons, and in the latter higher infestations were observed and required chemical control in some areas. Population surveys of S. sueroides in soybeans will be continued in the following seasons for monitoring its occurrence and expansion in the region. Basic research on the insect biology and host preference is highly encouraged since this information is still lacking for the Brazilian conditions. Ocorrência de lagarta das leguminosas em soja no norte do Brasil Resumo: Este estudo reporta a primeira ocorrência da lagarta-pinça Selenisa sueroides (Guenée) (Lepidoptera: Noctuidae) atacando plantas de soja no norte do Brasil, sendo seu segundo registro de ocorrência na cultura no país. O relato de sua ocorrência é proveniente de monitoramentos periódicos de pragas e inimigos naturais de soja por meio de batida de pano na região de Paragominas, estado do Pará, durante as safras 2015-2017. A presença de lagartas de S. sueroides foi registrada em todas as safras, sendo que na última safra altas infestações foram observadas, necessitando controle químico em algumas áreas. Levantamentos populacionais de S. sueroides em soja serão continuados nas safras seguintes para monitorar sua ocorrência e expansão na região. Pesquisa básica sobre a biologia e preferência hospedeira do inseto é altamente recomendada, uma vez que essas informações ainda estão faltando para as condições brasileiras.